2016
DOI: 10.1186/s12889-016-2826-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mean serum lipids among adults in Germany: results from National Health Surveys 1997-99 and 2008-11

Abstract: BackgroundMonitoring of serum lipid concentrations at the population level is an important public health tool to describe progress in cardiovascular disease risk control and prevention. Using data from two nationally representative health surveys of adults 18–79 years, this study identified changes in mean serum total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), and triglycerides (TG) in relation to changes in potential determinants of serum lipids between 1997–99 and 2008–11 in Germany.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 48 publications
2
10
0
3
Order By: Relevance
“…33,37 Accordingly, monitoring of lipid profile alterations is considered an essential public health tool for the prevention or reduction of the risk of CVD 38,39 despite a causal relationship and practical consequences for treatment are less clear. 40 In consistent with our findings, Panagiotakos et al indicated that MCC showed a weak correlation with hypercholesterolemia compared to HCC or very HCC. 33 Further and based on the evidences from recent studies, MCC is safe and beneficial in both healthy persons as well as patients with CVD or DM.…”
Section: Discussionsupporting
confidence: 93%
“…33,37 Accordingly, monitoring of lipid profile alterations is considered an essential public health tool for the prevention or reduction of the risk of CVD 38,39 despite a causal relationship and practical consequences for treatment are less clear. 40 In consistent with our findings, Panagiotakos et al indicated that MCC showed a weak correlation with hypercholesterolemia compared to HCC or very HCC. 33 Further and based on the evidences from recent studies, MCC is safe and beneficial in both healthy persons as well as patients with CVD or DM.…”
Section: Discussionsupporting
confidence: 93%
“…In Germany, the SCORE Deutschland risk charts were recently recalibrated on the basis of data from the population-based German Health Interview and Examination Survey for Adults 2008–2011 (DEGS1) and CVD mortality statistics from 2012 [ 8 ]. The need for an update arose from several trends including declining mortality rates for cardiovascular diseases, decreasing total cholesterol levels [ 9 ] and hypertension [ 10 ] and smoking prevalence [ 11 ] in the general population. Accordingly, the mean 10-year risk estimates for fatal cardiovascular diseases calculated with the recalibrated SCORE were almost one third lower compared to the older version and the percentage of high-risk individuals (with a SCORE ≥ 5%) declined from 5.2% to 2.6% when applied to the 40 to 65 year old DEGS1 population [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…При этом в отличие от общероссийских данных, не выявивших гендерных отличий по ГХС, распространенность ГХС в Красноярском крае среди женщин оказалась достоверно выше по сравнению с мужчинами. На этот счет данные зарубежных авторов также противоречивы: не обнаружено значимых гендерных отличий по распространенности ГХС на материале американской, индийской популяции, жителей Германии, в то время как китайские, корейские, бразильские исследователи зарегистрировали большую распространенность ГХС среди женщин [3,4,8,14,17,18]. В то же самое время, согласно китайскому национальному метаанализу [7] 2014 г., суммарная распространенность всех типов дислипидемий среди мужчин оказалась значительно выше.…”
Section: Discussionunclassified
“…Повышенный интерес к мониторингу основных показателей липидного обмена на популяционном уровне наряду с другими значимыми факторами риска КВЗ обусловлен тем обстоятельством, что это важное средство по оценке динамики контроля и профилактики кардиоваскулярных факторов риска [3].…”
unclassified